The Eigenfrequencies of a Real Structure Excited by an Internal Noise - Benabdelkader, Boufeldja; Elmir, Mohammed; Touhami, Abdelhamid (International Journal of Natural Sciences Research, 2015)
This research work attempts to present an experimental study on the structure of the former laboratory of vibration and structural dynamics in the technological hall that belong to Bechar University. This study tries to determinate the real behavior of this structure. The structure is exited by background noise generated by a vibrating table compacting concrete, placed inside the laboratory, after we simulate this noise with an electrodynamics shaker. The response of the structure was captured by a tri-axial accelerometer. The experimental results are presented under an auto spectrum, for determining the eigenfrequencies of the structure, this values are compared with those obtund from a numerical simulation bases on the finite elements method.